THE IMPACT OF SOCIAL MEDIA AND KNOWLEDGE ON ADOLESCENTS' INTENTIONS TO ENGAGE IN E-CIGARETTE SMOKING - Susanto, Agus; Mulyanto, Dody; Licia, Rizka (The Indonesian Journal of Public Health, 2025)
Introduction: The global prevalence of e-cigarette use among adolescents (11.3%) is increasing, primarily driven by exposure to promotional content on social media platforms. Aims: This study aimed to examine how exposure to e-cigarette content, content type, e-cigarette-related activity within the content, and knowledge about e-cigarettes influence adolescents’ intention to use e-cigarettes. Method: This survey-based study was conducted in Surakarta, Central Java, in November 2024. A total of 260 junior and senior high school students were selected through stratified random sampling. Data were collected using a structured questionnaire, and logistic regression analysis was applied to evaluate the relationships between variables. Results: The analysis indicated that exposure to e-cigarette content significantly increased the intention to use e-cigarettes (p < 0.001). In contrast, higher levels of knowledge about e-cigarettes were significantly associated with a lower intention to use them (p = 0.020). However, neither the type of content nor the presence of e-cigarette-related activity within the content showed a significant association with use intention (p = 0.501 and p = 0.162, respectively). The logistic regression model accounted for 25% to 34% of the variance in e-cigarette use intention, suggesting a moderate explanatory power. Conclusion: These findings underscore the significant influence of e-cigarette content exposure and adolescents’ knowledge levels on their intention to use e-cigarettes. While exposure increases the likelihood of use, adequate knowledge appears to reduce it. Therefore, reducing adolescents’ exposure to e-cigarette content and improving their awareness of the associated health risks may serve as effective strategies to prevent e-cigarette initiation.